Organic Combination of New Quality Productivity and Land Engineering - Zhang, Jing; Xia, Liheng (International Journal of Natural Resources and Environmental Studies, 2024)
New quality productivity is the fundamental driving force to achieve high-quality development. The organic combination of new quality productivity and land engineering is an important way to promote social development and ecological governance. The rational use of land engineering can realize the rational use and sustainable development of land resources, but the means of land engineering are relatively backward and cannot give full play to its role. It is necessary to use the new quality productivity to promote the development of land engineering, accelerate the construction of a new development pattern, and realize the efficient use of land resources in the aspects of technological innovation, optimizing resource allocation, promoting industrial upgrading, promoting sustainable development, policy support and personnel training.